Phase diagram of solid-phase transformation in amorphous carbon nanorods - Sorkin, Anastassia (2014)
The transformations of amorphous carbon nanorods with different diameters and densities upon heating up to different temperatures are studied with density-functional-based tight-binding molecular dynamics. Phase diagrams with assorted transformed sp2 nanostructures depending on both temperatures and line density, under different heating treatments, are presented to place the observations in perspective. Under instant heating, the lowest line density at which a carbon nanotube can form is 8 Å–1, while a double-walled carbon nanotube can form at a linear density of 19–20 Å–1 and higher. Under gradual heating, both partially unzipped carbon nanotubes and carbon nanoscrolls are formed as notable intermediate structural motifs. This work sheds light on the microscopic mechanism of various sp2 nanostructural formations with the featured motifs highlighted as important intermediates, which will serve as an important guide in producing graphene nanoribbons, single-walled and double-walled carbon nanotubes, and carbon nanoscrolls from amorphous carbon nanorods.